Analisis Sentimen Pada Ulasan Pengguna Aplikasi Streaming Vidio Menggunakan Metode Naïve Bayes - Muhammad Yusuf Siregar; Ade Davy Wiranata; Rizki Adi Saputra (STMIK Budi Darma, 2024)
The The development of information technology innovation has a positive impact on the media and entertainment industry, especially in the significant use of online streaming services. Vidio is one of the most popular streaming applications, providing interesting features such as watching, uploading, and sharing videos in mobile format for smartphones, tablets, and smart TVs. Vidio's strength is its ability to show live television from various channels in Indonesia. Although the Vidio app offers interesting features and ease of use, not all users are guaranteed to be satisfied. Each app has its own advantages and disadvantages, so users' experiences and views may vary. This can be seen from the user reviews available on the Google Play Store. This research aims to analyze the sentiment of user reviews of the Vidio application using the Naïve Bayes algorithm. The data used in this research are 1500 reviews collected in February 2024. After going through the data cleaning stage, the number was reduced to 1475 review data. From the available dataset, there are 165 positive reviews and 1310 negative reviews. The research process includes data retrieval using web scraping technique, data labeling, preprocessing, and TF-IDF weighting before the classification stage. For classification, cross validation technique and Naïve Bayes method were used. The results showed that the accuracy achieved by the Naïve Bayes algorithm was 80.28%, precision 24.18%, and recall 35.76%.